Dinâmica de transporte de sedimento não-uniforme em um micro-reservatório no semiárido - Almeida, Thais Rodrigues (2019)
The dynamics of the erosion process and sediment production in a watershed have great relevance for water resources management. All watercourses carry sediments with greater or lesser intensity, being responsible for the silting process. This process causes the reduction of the river trough and reservoir volume, thus compromising human supply, power generation systems, navigation. Therefore, there is interest in understanding the dynamics of hydrological and hydrosedimentological processes, especially in semiarid regions as they are important for the conservation and preservation of watersheds. Thus, the objective of the study was to evaluate the non-uniform sediment dynamics using the equation of Haan et al. (1994), in a micro-reservoir, upstream of the school dam, located at the Curu Valley Experimental Farm (FEVC) - Pentecoste / CE. The experimental part of the research was carried out with rainfall and hydrosedimentological data collection, soil samples and runoff during the rainy season in 2018 and 2019. The monitoring of soil erosion in the micro-reservoir, as well as the sediment deposition, was done with the use of erosion pins. In the micro-reservoir, were applied, sediment transport models proposed by Haan et al. (1994) and Fifield (2011). The results indicated that there was a change in the dynamics of the erosive process in relation to the monitoring performed in the study area. Comparative observation of the flow events monitored with the changes observed in the micro-reservoir riverbed that there is an interrelation between the events of larger flow rates and the erosion increase, compared to the events of smaller flow rates. From the spatialization of the physical parameters of the soil, it was possible to observer the dynamics of the erosion process and sediment deposition in the monitored area. The model proposed by Haan et al. (1994), showed good performance in sediment balance simulations for larger reservoirs, in the application to micro-reservoir scale, an overestimation of the deposited sediment was obtained.